Răspuns :
a = 1/3*c
a = c/3
a = 942/3
a = 314
b = a-146
b = 314-146
b = 168
d = b+1/2*b
d = b+b/2
d = 168+168/2
d = 168+84
d = 252
c-a+(d-b) = 942 - 314 + (252 - 168) =
628 + 84 = 712
a = c/3
a = 942/3
a = 314
b = a-146
b = 314-146
b = 168
d = b+1/2*b
d = b+b/2
d = 168+168/2
d = 168+84
d = 252
c-a+(d-b) = 942 - 314 + (252 - 168) =
628 + 84 = 712
a = c/3
b = a - 146
c = 942
d = b + b/2
a = 942/3 a = 314
b = 314 - 146 b = 168
d = 168 + 168/2
d = 168 + 84 d = 252
c - a + (d - b) = 942 - 314 + (252 - 168) = 628 + 84 = 712
b = a - 146
c = 942
d = b + b/2
a = 942/3 a = 314
b = 314 - 146 b = 168
d = 168 + 168/2
d = 168 + 84 d = 252
c - a + (d - b) = 942 - 314 + (252 - 168) = 628 + 84 = 712